The Effectiveness of Peer-Collaboration Learning Strategy and 21st Century Skill Knowledge on Pre-Service Teachers’ Academic Achievement in Integrated Science in Nigerian Colleges of Education - Samuel Olalekan Oyasola (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2022)
This study examined the effectiveness of peer-collaboration learning strategy and 21st century skill knowledge on pre-service teachers’ academic achievement in integrated science in Nigerian colleges of education. This research employed non-equivalent group pre-test-post-test quasi experimental design. The sample for this study was 80 integrated science pre-service teachers from two colleges of education selected for the study. The instrument used for data collection was Integrated Science Achievement Test (ISAT). One research question and two null hypothesis were formulated were designed to guide the study. Descriptive statistics of means and standard deviation were used to answer all the research questions. The results of the study showed that, peer collaboration learning strategy enhanced 21st century skills pre-service teachers’ and performance in Integrated Science better than conventional method. Integrated science lecturer should not only use peer collaborative strategy to teach the students the subject matter but should also allow them to interact with one another, so that they (students) can take charge of how they can learn. This can foster confidence in the students and enhance their achievement in integrated science.